The Nigerian State and Social Protection Under the Buhari Presidency (Journal of Management and Social Sciences, 2023)
Protecting the vulnerable constituencies against risks, hazards and poverty is a common practice across countries of the world, whether developed or developing. While social protection programming in Nigeria predates political independence, the social protection efforts of the Buhari administration remain the most comprehensive in the history of Africa’s largest economy. The expansive scope/coverage of the administration’s social protection programming is better appreciated when viewed within the context of rising social inequality and poverty in the country as amply evidenced by a recent report of the National Bureau of Statistics. This paper examines the social protection practice of the Buhari administration which was instituted in 2016. Using secondary data and official records, the paper finds that while the social protection programming of the regime is elaborate and ambitious, it has not substantially achieved its intended consequences. The paper identifies challenges impeding the social protection efforts and proposes some mitigating measures.